2016
DOI: 10.1007/s00345-016-1773-y
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma recurrences and metastases in primary non-metastatic patients: a population-based study

Abstract: In this population-based study, 21 % of the patients had metastatic disease at presentation, with a decreasing trend over the study period. During 5-year follow-up, 20 % of the primary non-metastatic patients had recurrent disease. Of the patients with recurrence, half were given systemic oncological treatment and 17 % underwent metastasectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
157
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 222 publications
(165 citation statements)
references
References 23 publications
3
157
0
5
Order By: Relevance
“…Concerning all stages of RCC, the most common locations of the first recurrence were lung (54%), lymph nodes (22%), bone (20%), and liver (15%). 75 Other population-based studies have found similar results. 76 Chin et al 77 reported that tumour stage plays an important role in timing of recurrence, with T1 tumours generally recurring between 3 and 4 years following resection.…”
Section: Recurrence Patterns For Pt1 Tumours (Low Risk)supporting
confidence: 59%
See 2 more Smart Citations
“…Concerning all stages of RCC, the most common locations of the first recurrence were lung (54%), lymph nodes (22%), bone (20%), and liver (15%). 75 Other population-based studies have found similar results. 76 Chin et al 77 reported that tumour stage plays an important role in timing of recurrence, with T1 tumours generally recurring between 3 and 4 years following resection.…”
Section: Recurrence Patterns For Pt1 Tumours (Low Risk)supporting
confidence: 59%
“…79 Among several studies regarding RCC surveillance, the latest postnephrectomy recurrence in the lungs, abdomen, and bone was approximately 6 years, 8 years, and 12 years, respectively. [75][76][77][78] In a cohort from a single center, most kidney cancer patients treated for lung metastasis were diagnosed with metachronous lesions with the following features: solitary mass, one affected lung, and measured more than 2 cm. Multivariate analysis confirmed a significant effect of radical surgery on the survival in these pateints.…”
Section: Cuaj -Cua Guidelinementioning
confidence: 99%
See 1 more Smart Citation
“…Ежегодно от рака почки умирают около 8 тыс. россиян [1].Несмотря на совершенствование методов диагнос-тики и миграции стадии заболевания в сторону повы-шения частоты выявления локализованных форм опу-холи, около трети пациентов имеют синхронные отдаленные метастазы на момент установления диаг-ноза и у 20-25 % развиваются метахронные метастазы в разные сроки после хирургического лечения [2,3].Наиболее распространенным (85 %) вариантом рака почки является светлоклеточный, характеризую-щийся мутацией гена VHL. Существующие достижения в терапии и рекомендации по лечению диссеминиро-ванного рака почки относятся именно к светлоклеточ-ному типу.…”
unclassified
“…Несмотря на совершенствование методов диагнос-тики и миграции стадии заболевания в сторону повы-шения частоты выявления локализованных форм опу-холи, около трети пациентов имеют синхронные отдаленные метастазы на момент установления диаг-ноза и у 20-25 % развиваются метахронные метастазы в разные сроки после хирургического лечения [2,3].…”
unclassified